A development of a mechatronic system to stimulate cognitive skills in children. - Roncalla, Sofia (2023)
Assisted robots for the treatment of learning for children are currently on the rise and this is thanks to the good potential that robots have to communicate and capture their attention. It is proposed to make a humanoid robot called Potts that will be developed in 3D printing and that can be developed in Peru to improve learning in children with autism spectrum disorder (ASD) in different parts of the country. The robot was manufactured in PLA material and has 8 degrees of freedom in addition to being able to have a graphical interface with the user using two touch screens of 3.5 and 7 inches. It will use a Raspberry Pi control and will have an audio system which can communicate various instructions to the children. An experiment was conducted to compare the efficiency of performing a dynamic practiced by a psychologist versus the proposed robot. As a result, it was obtained that the child obtained fewer wrong answers with the robot than with the psychologist (decrease of repetitions up to 50% less). In addition, the percentage of time that the child kept looking at the psychologist or the robot during the dynamic was calculated. A value of 85% was obtained for following the robot compared to 60% of the time that was spent with the psychologist.